2016
DOI: 10.1558/eap.v1i1.28747
|View full text |Cite
|
Sign up to set email alerts
|

Variability and multiplicity in the meanings of stereotypical gendered speech in Japanese

Abstract: Recent research on the use of gendered speech in Japanese has demonstrated extensive within-gender diversity, suggesting that the relationship between linguistic forms and gender is variable, not fixed. While this diversity in use suggests a diversity in interpretation, the latter has not been adequately examined in its own right and deserves closer attention, given that it has important implications for the relationship between linguistic forms and social meanings. To address this gap, this article analyses b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The use of the contracted form, together with ttū ‘say’ (the informal form of to yū or tte yū ‘say that’) in line 1 seems to emphasize his discontent about this fact. Okamoto (2016) and Okamoto and Sato (1992) reported that some young women used this contracted form, but when they did, they tended to qualify it by hedging (e.g., mitaina ‘like’) and/or with laughter, which suggests their ambivalent stance toward the norms for women's speech. In contrast, when the men in Okamoto's (2016) study used the contracted form (quite frequently), they did not qualify it at all.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of the contracted form, together with ttū ‘say’ (the informal form of to yū or tte yū ‘say that’) in line 1 seems to emphasize his discontent about this fact. Okamoto (2016) and Okamoto and Sato (1992) reported that some young women used this contracted form, but when they did, they tended to qualify it by hedging (e.g., mitaina ‘like’) and/or with laughter, which suggests their ambivalent stance toward the norms for women's speech. In contrast, when the men in Okamoto's (2016) study used the contracted form (quite frequently), they did not qualify it at all.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest a greater effect of gender norms on the two female speakers in MGCs than in SGCs. Furthermore, although none of the women or men in the study used the strongly masculine forms zo and ze, previous studies have reported that (young) women occasionally use them and that when they do, they often accompany the forms with a hedge or laughter (Okamoto, 1995(Okamoto, , 2016, suggesting that these women are aware they are breaking a norm. Thus, although the gender categories of the SFFs in Table 2 may require revision as norms for contemporary (standard Japanese-speaking) women, they still may be relevant depending on the situation and on the SFF.…”
Section: Negotiating Norms In Practicementioning
confidence: 89%
See 2 more Smart Citations
“…Obviously, Japanese speakers are not automata and do not always conform to these linguistic gender norms in practice for a variety of reasons, as has been demonstrated by a number of empirical studies (e.g. Okamoto 1995Okamoto , 2016Shibamoto Smith 2004, 2016;Miyazaki 2004;Mizumoto 2006;Okada 2008;Sunaoshi 2004;Abe 2010).…”
Section: Stereotypically Gendered Linguistic Forms In Japanesementioning
confidence: 99%